Dinamika Kehidupan Anak-Anak Pada Masa Jawa Kuna Abad VIII – XV Masehi - Boedhijono, S. Kusparyati; Maulana, Hariani Santiko Ratnaesih; Wuryantoro, Edhie; Rahardjo, Wanny (UI Scholars Hub, 2008)
There were not many researchers focus on the children’s life in the ancient times. This research was done based on that fact. Objective of this research is to comprehend the children’s roles in the ancient time, in their daily activities. Daily activities that included in this research are: child and nurture, child and education, child and home activities, child and health, and, child and religion. This research was done based on the artifacts’ data and textual data. Artifacts’ data are statues and reliefs, while textual data are written stories about children; i.e. inscriptions and ancient manuscripts in ancient Java language and mid-ancient Java language. Three main objects of research are: children’s profile identification, community environment in where they lived, children’s daily life. Research methodologies are: data collection, data processing, and data interpretation.